A Systematic Review of the Peer-Reviewed Literature on Self-Blame, Guilt, and Shame. (September 2015) - Duncan, Catherine; Cacciatore, Joanne
This is the first systematic review of the evidence on the prevalence of self-blame, guilt, and shame in bereaved parents. A search of PsychINFO, MEDLINE, Embase, CINAHL, PubMed, and Science Direct resulted in 18 studies for the period 1975 to 2013 which the authors have appraised. Self-blame, guilt, and shame are common in bereaved parents, albeit to varying degrees, with differential relationships to sex, and diminishing over time. There is some evidence that guilt and shame predict more intense grief reactions and that self-blame predicts posttraumatic symptomology, anxiety, and depression in bereaved parents. Heterogeneity of the studies and numerous methodological concerns limit the synthesis and strength of the evidence and the generalizability of the findings. Self-blame, guilt, and shame are commonly experienced by bereaved parents. Awareness of these affective states may assist clinicians in the identification of bereaved parents who are at a higher risk of developing adverse psychological outcomes. Overall, self-blame, guilt, and shame have received very little attention in the bereavement research, leaving many unanswered questions. Implications for practice and recommendations for future research are discussed.